Systems - Melnikova, Daria; Naivo, Ēriks; Lavrinovičs, Andrejs 1987-; Lavrinovičs, Andrejs 1987-; Kurševa, Maija 1981-; 108 1978-; 1010 1979-; Loumeau, Arnaud 1978-; Brunner, Bianca 1974-; Niederkofler, Daniél; Méndez Alonso, David 1988-; Janković, Dunja 1980-; et al. ([Popper magazine], 2015)
"This issue is dedicated to contemporary and post-internet art with abstract forms, color, geometry, mathematically generated images, visualizations generated by biological processes and outer space." (Verlagsseite)